2004
DOI: 10.1021/jp049276+
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Predissociation Spectroscopy of Large Water Clusters:  A Unique Probe of Cluster Surfaces

Abstract: The vibrational OH-stretch spectra of large water clusters were measured by photofragment spectroscopy after the absorption of pulsed tunable infrared radiation in the frequency range from 3000 to 3800 cm -1 . The mean size of the clusters from 〈n〉 ) 20 to 1960 was measured by threshold photoionization of the water clusters doped with sodium atoms. The largest abundance of the fragments was that of water hexamers. The fragment intensities are measured for different excitation energies and different cluster tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
85
3
3

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 74 publications
(148 reference statements)
15
85
3
3
Order By: Relevance
“…In accordance with these discussions, we suggest that formation of crystalline structures occurs in H + (H 2 O) n clusters with hundreds of water molecules. Such formation of a crystalline core in large clusters has been predicted by theoretical searches for low-energy structures and IR spectroscopy on average size-controlled clusters, [2][3][4]22] and the present results are consistent with these previous studies. Figure 3 plots the free OH stretching frequencies as a function of the cluster size.…”
supporting
confidence: 93%
See 3 more Smart Citations
“…In accordance with these discussions, we suggest that formation of crystalline structures occurs in H + (H 2 O) n clusters with hundreds of water molecules. Such formation of a crystalline core in large clusters has been predicted by theoretical searches for low-energy structures and IR spectroscopy on average size-controlled clusters, [2][3][4]22] and the present results are consistent with these previous studies. Figure 3 plots the free OH stretching frequencies as a function of the cluster size.…”
supporting
confidence: 93%
“…The frequency seems to converge to 3699-3700 cm À1 . In the previous study on H + (H 2 O) n (n 100), from the fact that the OH frequency of 3699-3700 cm À1 is much lower than the previously reported value of about 3718 cm À1 for (H 2 O) hni=40,111 (hni: average size, Figure 3), [4] we concluded that an excess proton affects the structures of H-bonded network even in large clusters (n = 100). [10] To obtain more accurate data on the free OH frequency of large neutral water clusters, we recently measured free OH frequencies of phenol-(H 2 O) n clusters, in which the perturbation from phenol is negligible.…”
contrasting
confidence: 64%
See 2 more Smart Citations
“…6,26,27 We obtained mean cluster sizes of N = 58 for the 40 eV data set, and N = 84 for both 60 eV data set (more details are available in the supplementary material 28 ). For the 40 eV data set, the nozzle temperature had to be estimated from the heating power, instead of a thermocouple reading.…”
Section: Methodsmentioning
confidence: 99%